Flumazenil in treatment benzodiazepine withdrawal syndrome: Case report - Ramah Aleksandar J.; Todorović Mirjana M.; Crnić Katarina B. (Srpsko lekarsko drustvo, 2015)
Background: Today in the world and in Serbia is growing number of people who are addicted to benzodiazepine. A particular problem is the process of detoxification and treatment of benzodiazepine withdrawal syndrome due to a recurrence of symptoms of anxiety disorder, availability of benzodiazepines, falling motivation. Standard procedures have often proved unsuccessful and the last decade, and the search for new protocols, including the flumazenil, benzodiazepine receptor antagonist, is actualized. Case report: The patient aged 48 years was admitted to the specialist psychiatric clinic, for treatment of benzodiazepine addiction. Anxiety disorder was diagnosed since adolescence perennial addiction on benzodiazepines and the initial withdrawal syndrome. Former motivated topical treatments for detoxification were unsuccessful. The presence of dual diagnosis, persistence of both disorders in perennial cycle, treatment resistance and actual motivation contributed to the decision to opt rapid detoxification from benzodiazepines by flumazenil application protocol, for hospital treatment by adjuvant therapy with lamotrigine. After discharge from hospital in stable condition it was with no signs of withdrawal syndrome and a rebound of anxiety symptoms. Lamotrigine medication continued including CBT, held during the one-year abstinence monitoring, with sufficient social functionality. Discussion: The efficacy and safety of flumazenil in the treatment of benzodiazepine withdrawal syndrome was investigated in numerous clinical trials, and the mechanism of action is complex, from the benzodiazepine antagonist to inverse agonist in certain circumstances, as well as 'up-regulation' receptors, which together leads to a reduction in symptoms of abstinence syndrome and anxiety in the longer term after treatment, thereby acting favorably to the adherence and remission. Conclusions: Flumazenil protocol is an efficient method in the treatment of the benzodiazepine withdrawal syndrome. Given the existence of certain concerns and relatively little experience in this procedure, it is necessary to define further all aspects of the procedure.